A gamificação no desenvolvimento de aplicações móveis para smartphones e tablets - Kadow, André Luis Dal Santo (2014)
The concept of gamification applied to mobile devices is extremely new, in view that cell phones began to offer the necessary characteristics to an effective project since the second half of last decade through a major interactivity, new interfaces and communication performed through the principle of location due to the arrival of 3G. The main idea of this work is the design and the concepts of gamification, its similarities and differences comparing to electronic games and its applicability through mobile devices. The result will be a study of the current conditions and the future of gamification. This research is based on a methodology that analyzes application data and performs field surveys. Among the mobile devices applications that use gamification effectively, Zombies, Run!, Foursquare, FuelGood, Waze and Nike+ Running can be mentioned. The latter two will be the objects of study of this essay since they are applications with a big and extremely active users base, facilitating data collection in several layers. This analysis was held based on contributions from Henry Jenkins, Lucia Santaella, Werbach and Pierre Levy about social networking, participative culture and collective intelligence and takes into consideration the from Paul Schuytema about the concept of electronic games and Johan Huizinga about the psychology of games, among other authors